Mesa-Lago, Carmelo (2008): Reassembling social security: a survey of pensions and healthcare reforms in Latin America. Oxford University Press - Martínez Franzoni, Juliana (2009)
Reseña del libro de Mesa-Lago, Carmelo (2008): Reassembling social security: a survey of pensions and healthcare reforms in Latin America. Oxford University Press.